Consumption and Unemployment - Dynarski, Mark; Sheffrin, Steven M. (Quarterly Journal of Economics, 1987)
This paper examines consumption changes of workers following experiences of unemployment in different stochastic environments. The model developed in the paper predicts that consumption changes following unemployment spells should be small for workers the higher are their layoff and recall probabilities. These predictions are confirmed in estimates with panel data.